A Novel of Calculating the Optimal Number of Virtual Servers to Improve Resources Usage in Cloud Computing - A. G. Al-Khulaidi, Abdualmajed; Al-Shalabi , Ahmed A.; Nasser , Adel A.; Nasser , Adel A.; Sarhan Al-Duais, Mohammed; N. Ali , Mansoor; AL-Khulaidi , Nesmah A. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Recently, there has been a major revolution in cloud computing, where most companies have become dependent on cloud computing because of its importance in saving resources and reducing expenses. The research dealt with the problems of optimal allocation of resources within the cloud environment. Experiments have shown that the optimal number of virtual servers to be placed on the physical server to be presented to the user are the advantages of using algorithms to place virtual machines on computing servers online to save money, make maximum use of resources, and avoid system overload. As it was also observed in the case of offline algorithms for placing virtual machines on the actual server, it was concluded that the NFD algorithm is the best in the case of problem size 300 * 300, number of nodes L = 6 nodes, time T = 0.55, and algorithm accuracy R = 1.700. The optimal number of virtual servers to be placed on the physical server is four nodes. This indicates that online algorithms for placing virtual machines on the physical server work better in cloud computing. Research has demonstrated that the advantages of having the ideal number of virtual servers installed on the physical server that the user sees.